Genetic analysis of an ephemeral intraspecific hybrid zone in the hypervariable tree, Metrosideros polymorpha, on Hawai‘i Island - Stacy, E A (Heredity (Edinb), 2016)
Intraspecific hybrid zones involving long-lived woody species are rare and can provide insights into the genetic basis of early-diverging traits in speciation. Within the landscape-dominant Hawaiian tree, Metrosideros polymorpha, are morphologically distinct successional varieties, incana and glaberrima, that dominate new and old lava flows, respectively, below 1200 me on volcanically active Hawai‘i Island, with var. glaberrima also extending to higher elevations and bogs. Here, we use morphological measurements on 86 adult trees to document the presence of an incana–glaberrima hybrid zone on the 1855 Mauna Loa lava flow on east Hawai‘i Island and parent–offspring analysis of 1311 greenhouse seedlings from 71 crosses involving 72 adults to estimate heritabilities and genetic correlations among vegetative traits. Both the variation in adult leaf pubescence at the site and the consistency between adult and offspring phenotypes suggest the presence of two hybrid classes, F(1)s and var. incana backcrosses, as would be expected on a relatively young lava flow. Nine nuclear microsatellite loci failed to distinguish parental and hybrid genotypes. All four leaf traits examined showed an additive genetic basis with moderate to strong heritabilities, and genetic correlations were stronger for the more range-restricted var. incana. The differences between varieties in trait values, heritabilities and genetic correlations, coupled with high genetic variation within but low genetic variation between varieties, are consistent with a multi-million-year history of alternating periods of disruptive selection in contrasting environments and admixture in ephemeral hybrid zones. Finally, the contrasting genetic architectures suggest different evolutionary trajectories of leaf traits in these forms.